The Influence Of Sustainable Marketing On Customer Loyalty With Brand Image And Customer Satisfaction As Mediating Roles: Paint Industry In Indonesia - Bambang Wisnu Aji (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the influence of sustainable marketing on customer loyalty, with brand image and customer satisfaction as mediating variables, using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. Data were collected from 311 respondents who are customers of Propan paint products. The results show that economic sustainability and social sustainability do not have a significant effect on customer loyalty. In contrast, environmental sustainability has a significant influence on customer loyalty. Furthermore, brand image and customer satisfaction sequentially mediate the effect of economic sustainability and social sustainability on customer loyalty. However, both mediating variables do not significantly mediate the effect of environmental sustainability on customer loyalty. These findings offer important implications for sustainable marketing strategies, particularly in the paint industry.